-2(3-2b)-3(1-b)=40

Simple and best practice solution for -2(3-2b)-3(1-b)=40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3-2b)-3(1-b)=40 equation:


-2(3-2b)-3(1-b)=40

We simplify the equation to the form, which is simple to understand
-2(3-2b)-3(1-b)=40

Reorder the terms in parentheses
+(-6+4b)-3*(1-b)=40

Remove unnecessary parentheses
-6+4b-3+*(+1-b+)=+40

Reorder the terms in parentheses
-6+4b+(-3+3b)=40

Remove unnecessary parentheses
-6+4b-3+3b=+40

We move all terms containing b to the left and all other terms to the right.
+4b+3b=+40+6+3

We simplify left and right side of the equation.
+7b=+49

We divide both sides of the equation by 7 to get b.
b=7

See similar equations:

| 1-4p-3/4= | | 3L+w=400 | | -2(3-2b)-3(1-b)=49 | | a(3x-8)= | | 4x+2(x-6)=8x+2 | | -5(4+4x)=-140 | | 9x^5-12x^4-21x^3=0 | | 2x+134=180 | | 3a-7=5a+9 | | 8u=3u-35 | | -3(v+6)-6(-7+4v)=-57 | | -4(-4+x)=-24 | | 3x-5x+7=39 | | 6ac-2bd+4bc-3ad=o | | 24=3x+12-x-7 | | 2x+30=3x+20 | | 2(x-2)+15=5 | | 44=-4(2x-4)+3(1+x) | | 7(x+2)=3x | | x=300+-2y | | 19-x=22-2x | | 40-5x=8x | | 7+5p=2p-5 | | 4(6n+9)-10n=0 | | 67=7(7-6x)+3(x+6) | | x^2+22x-180=0 | | 6x+5=2x+13 | | 8x-8y= | | (2-4)+1=-11 | | 1+10x^2+x^4=0 | | 6(6t+3)=9(4t+2) | | 3(3-3x)=9 |

Equations solver categories